Formulasi Micellar Based Water Ekstrak Bunga Telang - Muhammad Dzakwan (Parapemikir : Jurnal Ilmiah Farmasi, 2020)
Clitoria ternatea is a twining herbal medicinal plant. It has pharmacological activity as antioxidant, anticancer and anti depressant. Extracts of C ternatea flowers were used as a component of cosmetics. The aim of this research is to formulate and develop micellar based water with variation concentration of amphiphilic polymer. Results showed that formulation containing amphiphilic polymer 1% (F5) is the most stable, clearly, particle size distribution of 46,67 nm and zeta potential -18,4 mV was obtained. Conclution, extracts of C ternatea flowers successfully formulaed to  micellar based water, antioxidant activity (IC50) of 1,30 mg/ml was obtained.